Ventricular Septal Defects in Adults: A Bedside Case Discussion for Residents - Prerna Garg; Aatish Rengan; Hitesh Srinivasan (Journal of the Practice of Cardiovascular Sciences)
A young boy presented with palpitations and shortness of breath. He had a history of recurrent chest infections as a child. The clinical approach to such a patient along with correlation from investigations is discussed as a teaching exercise for cardiology fellows in training.